Reinterpretasi : Motif Pucuak Rabuang pada Media Teko - Heru Ningrum; Dharsono Dharsono; Wilma Sriwulan (Besaung : Jurnal Seni Desain dan Budaya, 2018)
AbstractThe creation of ceramic craft motifs of pucuak rabuang motif is a reinterpretation of the philosophy of the Minangkabau tradition "nan bak pucuak rabuang, ketek baguno gadang tapakai” (like a small, useful little bamboo shoot). Through this tradition, it became a source of inspiration for the creators in the creation of ceramic craft art. The motive of pucuak rabuang is a motive with aesthetic and philosophical values, so it needs to be presented again in the art of ceramic craft. The author revealed the philosophical form and meaning of the pucuak rabuang motive through teapot media. The motif of pucuak rabuang is also found in the gadang house and the sarong head, the bottom of the sarong at the end of the scarf or clothing. The motif of pucuak rabuang is useful for the lives of Minangkabau people. With the motive of pucuak rabuang through sociological analysis and an aesthetic approach, it can be said that the presence of the Minangkabau motif of pucuak rabuang has aesthetic value and also expresses various meanings and customs functions as one of the identities of the Minangkabau people.Keyword : Reinterpretation, Motive Pucuak Rabuang,Teapot Abstrak Penciptaan seni kriya keramik motif pucuakrabuang ialah reinterpretasi kembali filosofi adat istiadat Minangkabau “nanbak pucuak rabuang, ketek baguno gadang tapakai (bagaikan pucuk rebung, kecil berguna besar terpakai). Melalui adat istiadat ini menjadi sumber inspirasi pengkarya dalam penciptaan seni kriya keramik.Motif pucuak rabuang merupakan motif dengan nilai estetis dan filosofis, sehingga perlu dihadirkan kembali dalam karya seni kriya keramik.Pengkarya mengungkap kembali bentuk dan makna filosofi pada motif pucuakrabuangmelalui media teko.Motif pucuak rabuang juga terdapat di rumah gadang dan kepala kain sarung, bagian bawah sarung pada ujung selendang atau sandang.Motif pucuak rabuangberguna bagi kehidupan masyarakat Minangkabau.Dengan adanya motif pucuakrabuangmelalui analisis sosiologis dan pendekatan estestis dapat dikatakan bahwa kehadiran motif pucuak rabuang Minangkabau memiliki nilai estetis juga mengisyarakan berbagai makna dan fungsi-fungsi adat istiadat sebagai salah satu identitas masyarakat Minangkabau.Kata kunci: Reinterpretasi, Motif Pucuak Rabuang, Teko